Benefit Realization Model of Information System Strategic Planning Success: A Proposed Model - Bernadus, Gunawan Sudarsono; A'ang, Subiyakto; Aedah, Abd Rahman (2020)
Information System Strategic Planning (ISSP) is an effort to build an organization or institution in achieving and realizing success such as aligning information system (IS) with business strategy, competitive advantage, effectiveness, capability, flexibility, improving performance, increasing competitive advantage by planning multiple systems information that has a value of success in a certain time either short or long term. In this study, we have tried to propose a model that adopts the successful of DeLone and McLean information system model (DMSISM) to be adopted into a proposed model, namely the ISSP benefit realization success model (ISSPBRM). The success of ISSP which is the goal of ISSPBRM contains the key to PSSI's success, which includes formal methods and implementation so that it is very suitable to adopt DMSISM which also includes conceptualization and operationalization of information system success.